منهج ابن الأثير في تناول الشاهد الشعري المثل السائر أنموذجاً - رجاء الله سلمي, عبد الرحمان (Revues faculté des lettres et des langues, 2017)
ملخــــــص:      تهدف هذه الدراسة إلى محاولة استخلاص المنهج الذي تميز به ابن الأثير في التعامل مع الشاهد الشعري باعتباره ميدانا للدرس البلاغي والنقدي، وهو منهج ينهض على ركائز متعددة ويتسم بخصائص مميزة تفضي إلى الكشف عن أسرار الشاهد، ونسيجه المعرفي، وتميزه عن غيره من الشواهد، والسعي إلى سبر أغواره وإماطة اللثام عن جمالياته. وكل ذلك يدل على ذوقه المميز في حسن اختياره أولاً، ثم في اتخاذه الشواهد الشعرية مدونة أدبية لمناقشة القضايا البلاغية والنقدية.                                                                                                                Abstract :  This study aims at attempting to draw the approach that characterized Ibn al – Athir’s dealing with the witness of poetry as a field of rhetorical and critical academic lesson. It is an approach that relies on multiple stilts, and distinguished by certain attributes conductive to reveal the secrets of the witness, its cognitive fabric, and its distinction from other witnesses or evidences; Seeking to fathom its depths, and uncover its aesthetics. All of this shows Ibn al – Athir’s distinctive taste in choosing these witnesses, and transferring them into a literary corpus to discuss rhetorical and critical issues